Social functioning and autonomic nervous system sensitivity across vocal and musical emotion in Williams syndrome and autism spectrum disorder - Järvinen, Anna; Ng, Rowena; Crivelli, Davide; Neumann, Dirk; Arnold, Andrew J.; Woo-VonHoogenstyn, Nicholas; Lai, Philip; Trauner, Doris; Bellugi, Ursula (Developmental psychobiology, 2016)
ABSTRACT Both Williams syndrome (WS) and autism spectrum disorders (ASD) are associated with unusual auditory phenotypes with respect to processing vocal and musical stimuli, which may be shaped by the atypical social profiles that characterize the syndromes. Autonomic nervous system (ANS) reactivity to vocal and musical emotional stimuli was examined in 12 children with WS, 17 children with ASD, and 20 typically developing (TD) children, and related to their level of social functioning. The results of this small‐scale study showed that after controlling for between‐group differences in cognitive ability, all groups showed similar emotion identification performance across conditions. Additionally, in ASD, lower autonomic reactivity to human voice, and in TD, to musical emotion, was related to more normal social functioning. Compared to TD, both clinical groups showed increased arousal to vocalizations. A further result highlighted uniquely increased arousal to music in WS, contrasted with a decrease in arousal in ASD and TD. The ASD and WS groups exhibited arousal patterns suggestive of diminished habituation to the auditory stimuli. The results are discussed in the context of the clinical presentation of WS and ASD. © 2015 Wiley Periodicals, Inc. Dev Psychobiol 58:17–26, 2016.